Konsep Walid dan Cara Menjaga Kehormatannya dalam Al-Qur’an Perspektif Tafsir Al-Qurthubi - Ahmad Nadif Muhlisin; Achmad Khudori Soleh (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The phenomenon of adolescent moral decline and the crisis of children's adab toward parents in the digital era highlights the urgency of extracting character education values from authoritative Islamic sources. This study aims to analyze the concept of walid in the Qur'an and its pedagogical values through the lens of Al-Qurthubi's Tafsir as a foundation for children's character education in their relationship with parents. This research employs a qualitative approach using library research and content analysis, conducted through four systematic procedures: (1) collection of Qur'anic verses, (2) contextual categorization, (3) inference through Tafsir Al-Qurthubi, and (4) drawing pedagogical conclusions. The findings reveal three key results. First, the Qur'an employs twelve variant forms of the word walid, reflecting the depth of the parent-child relational dimension in Islam. Second, the word walid appears in seven distinct contexts encompassing commands to honor parents, rights and obligations, stories of the Prophets, the story of Luqman, bequests and inheritance, supplications, and divine oaths each corresponding to a specific character education goal. Third, Al-Qurthubi's Tafsir identifies five primary ways to preserve parents' honor filial piety and kindness, gentle speech, refraining from harm, supplication, and protecting their good name which pedagogically represent strategies of habituation and modelling in children's character formation. This study contributes to the development of Islamic Education by offering an integrative model between classical tafsir and contemporary character education theory, while providing practical implications for Muslim educators and parents in designing Qur'an-based moral education.